Siblings of youth with a disability during the transition to adulthood: A synthesis of resources and understanding of their experiences to support them in current and future roles - Nguyen, Linda (My University, 2022)
As youth with disabilities age and transition to adulthood, they will often need to learn how to manage their healthcare. Siblings are members of the family who can provide support to their sibling with a disability, but their roles during transition have not been well described in the literature. Typically developing (TD) siblings identified that they require information and resources in their roles. The overall objectives of the research studies in this doctoral dissertation are: 1) to synthesize existing resources and programs to support TD siblings of individuals with a disability; and 2) to develop a deeper understanding about the experiences of TD siblings. The findings from these studies are summarized in six scholarly manuscripts prepared for peer review and publication. All studies were conducted in partnership with siblings with lived experiences. Results from the review and qualitative document analysis of online resources to support TD siblings (Chapter 2) identified that limited resources are available to support TD siblings with healthcare management of their sibling with a disability. The scoping review (with the protocol described in Chapter 3 and results presented in Chapter 4) identified that programs for TD siblings are focused on knowledge development and skill acquisition for the TD siblings themselves or on empowerment by training TD siblings in skills that they can apply with their sibling with a disability. In addition to synthesizing existing knowledge, the qualitative study provided an in-depth understanding of the experiences of TD siblings (with the protocol described in Chapter 5) in two distinct areas: their roles and responsibilities (Chapter 6) and the influence of their sibling and family relationships on their identity formation during developmental stages (Chapter 7). Overall findings from this dissertation suggest areas for future directions, including knowledge transfer to share synthesized resources with target audiences, co-creation of resources to support siblings in their roles, and enhancement of programs to involve siblings and the whole family.
Keywords: children, youth, siblings, patient-oriented research, program, case study, qualitative, knowledge synthesis, disability, healthcare transition